Working Document: Strategic Options in Education at the Regional Level - CARICOM (CARICOM Secretariat, 1992)
This document is formed by and addresses recent initiatives that have sought to develop regional and sub-regional approaches to educational reform, viz. The World Bank Study on “Access, Quality and Efficiency in Education in the Caribbean”, the OECS Education Reform Strategy and proposals made by the CARICOM Advisory Task Force on Education. It identifies the main issues and the principal policy recommendations that emanate from these initiatives, and presents strategic options for regional educational development. The paper is divided into four sections: Section 1 describes the context for education in the region; Section 2 summarizes the issues identified by the three initiatives; Section 3 lists the recommendations made in the OECS Reform Strategy and the World Bank Study; and Section 4 provides a listing of strategic policy options based on the recommendations in Section 3 and proposals of the CARICOM Task Force.
Keywords: CARICOM Advisory Task Force on Education